God-Botherers and Other True-Believers Gandhi, Hitler, and the Religious Right. - Bailey, F. G. (New York : Berghahn Books, Inc., 2008)
When reason fails to guide us in our everyday lives, we turn to faith, to religion; we close our minds; we reject austere reasoning. This rejection, which is a faith-based social and intellectual malignancy, has two unfortunate consequences: it blocks the way to knowledge that might enhance the quality of life and it opens the way to charlatans who exploit the faith of others. Examining two unquestionable malignancies of "the Christian Right" in present-day politics in the United States and the "secular religion" of Hitler's National Socialism, as well as the third, more complex case of Gandhi.
Title page-God-Botherers and Other True-Believers; Contents; Acknowledgements; Introduction; PArt I-Faith and Politics; Chapter 1-Faith, Reason and Consequences; Chapter 2-Religion and Persuasion in Politics; Part II-Antagonistic Religions; Chapter 3-Desert, Marketplace and Forum; Chapter 4-The Need for Enemies; Part III-A Religion of Love; Chapter 5-Gandhi; Chapter 6-Gandhi's Charisma; Chapter 7-Gandhi's Religion and Political Reality; Chpater 8-The First Cause and the Last Word; References; Index.
Description based on print version record.
Keywords: Religion; Political Science; Gandhi, -- Mahatma, -- 1869-1948.; Hitler, Adolf, -- 1889-1945.; Religion and politics; Religious fundamentalism; Religious right -- United States; Christian conservatism -- United States; National socialism; POLITICAL SCIENCE / Political Process / Political Advocacy; Electronic books